Skilled Migrants and Negotiations: New Identities, Belonging, Home and Settlement. (4th March 2019) - Webb, Susan; Lahiri-Roy, Reshmi
ABSTRACT: Issues of identity, home and belonging underline most transnational and transmigrational experiences. Globally, there is increasing interest in issues related to the settlement of migrants; yet there is growing evidence on a quotidian basis that migrant settlement into a host country is not a smooth experience. Drawing on qualitative empirical work, involving a large cross section of ethnically diverse skilled migrants located in a regional Australian centre, this article explores the issue of settlement through considering how the concepts of identity, belonging, settlement and home are presented in narrative accounts from skilled migrants to Australia. Intersectional theoretical frameworks are used to explore migrants' perceptions of identity, belonging and home in negotiating and realising their new settlement. This also helps highlight the differences in skilled and non-skilled experiences using visa status, gender, education, ethnicity and socio-economic status/class to conduct an intersectional analysis.